2020
DOI: 10.1177/2056305119897321
|View full text |Cite
|
Sign up to set email alerts
|

Beyond “I Agree”: Users’ Understanding of Web Site Terms of Service

Abstract: Whether they know it or not, the legal rights and responsibilities of users of websites and services, including social media, are defined and controlled by the terms of service of these online service providers. But despite the importance of these provisions, studies have shown that users rarely review terms of service, or think about their meaning. This study took advantage of a major website’s “simplification” of its terms of service to determine whether the changed language increased users’ understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This study affirms much of what is known about privacy, viz. people struggle to understand the terms in privacy policies [88] as well as the potential uses of their data [72]; they are more protective of privacy in the abstract [1]; people disclose personal information to services considered 'socially relevant' [99] (also [81]), and they continue to use services deemed useful despite inconsistencies with their privacy preferences [106]; they resolve discomfort regarding the collection of personal data [37] in part through a 'bandwagon heuristic' [98] and in part through a logic of free market economics [3]; they in fact do care about their privacy and try in their way to protect it [70], though they also feel they have little choice but to consent [27,47,104,114]. 9 There is, arguably, still value in showing how these are drawn together in participants' accounts, though our primary contribution is revealing the complicated relation between privacy and trust.…”
Section: Discussionmentioning
confidence: 99%
“…This study affirms much of what is known about privacy, viz. people struggle to understand the terms in privacy policies [88] as well as the potential uses of their data [72]; they are more protective of privacy in the abstract [1]; people disclose personal information to services considered 'socially relevant' [99] (also [81]), and they continue to use services deemed useful despite inconsistencies with their privacy preferences [106]; they resolve discomfort regarding the collection of personal data [37] in part through a 'bandwagon heuristic' [98] and in part through a logic of free market economics [3]; they in fact do care about their privacy and try in their way to protect it [70], though they also feel they have little choice but to consent [27,47,104,114]. 9 There is, arguably, still value in showing how these are drawn together in participants' accounts, though our primary contribution is revealing the complicated relation between privacy and trust.…”
Section: Discussionmentioning
confidence: 99%
“…But just as this is an example of success, it is also an example of the embedded problems associated with safeguarding digital rights. The notification to accept cookies, instead of being a protective measure, is instead a further mechanism normalizing the collection of data through "user consent" [86,87]. Just as most users fail to read the terms and conditions for most products and services due to their length and linguistically obtuse language, so too do users accept tracking cookies on web platforms.…”
Section: Losing Utopia: the Regression Of Digital Human Rightsmentioning
confidence: 99%
“…Yet, evidence from prior research work showed that online users have no/little knowledge about the data companies and digital technologies track, collect, and store about them (Gordon, 2018;Demmers et al, 2018;Boerman et al, 2018;Urban et al, 2019;Moran, 2020;Luria, 2023;Hartman-Caverly and Chisholm, 2023;Kumar, 2023), nor the regulations and rights related to information privacy (Prince et al, 2023;Robinson and Zhu, 2020;Soumelidou and Tsohou, 2021;Kardos, 2021;Maier et al, 2023). Further, prior recent studies evidenced thatto dateno research has been found that surveyed the impact of GDPR on users' control over personal data flows with few exceptions (Ooijen and Vrabec, 2019;Bornschein et al, 2020;Kretschmer et al, 2021) though they stressed the need for such investigation.…”
Section: Introductionmentioning
confidence: 99%